GROWTH AND PRODUCTIVITY OF INERIE KIDNEY BEAN IN THE LOWLANDS GIVEN WITH NPK FERTILIZER AND “AMAZING BIO GROWTH” BIOSTIMULANT - Yosefina Lewar; Ali Hasan; Jacqualine A. Bunga; Stormy Vertygo (Jurnal Penelitian Pertanian Terapan, 2020)
The kidney bean plants in East Nusa Tenggara (NTT) are generally cultivated in the highlands, whereas the areas in NTT are dominated by lowlands with extensive dryland agro-climatic conditions. Kidney beans are suitable for planting in areas with wet climates with varying altitudes. The suitable altitude is 1000-1500 hasl. However, it turns out that several research results showed that kidney beans can be grown in dryland or lowland ricefields with low production. During the growth of kidney bean plants, apart from the micro-climate that affects plant growth, the elements of production field management are also very important to support plant growth, such as balanced nutrient management. One of the technologies studied to increase production is NPK Phonska fertilization and Amazing Bio Growth biostimulant. The purpose of this study was to examine the dosage of NPK Phonska fertilizer and the best Amazing Bio Growth biostimulant concentration on the growth and yield of Inerie kidney bean seeds in the lowlands. The factors studied were the NPK Phonska (N) dose consisting of 3 levels, namely: N1: 300 kg / ha; N2: 250 kg / ha; N3: 200 kg / ha. And the concentration factor of ABG (B) biostimulant consisted of 4 levels, namely: B1: 2 cc/liter of water; B2: 4 cc/liter of water; B3: 6 cc/liter of water; and B4: 8 cc/liter of water. The results of the study informed that the dose of 250 kg/ha NPK Phonska gave the best 2 MST plant height (26.20 cm), 2 and 4 WAP stem diameter (3.64 mm and 5.85 mm), and the number of filled pods (15.52). pod). The concentration of ABG biostimulant 8 ml / l of water gave the best 4 WAP plant diameter (5.61 mm). The interaction between the NPK Phonska dose of 250 kg/ha and the concentration of ABG biostimulant 6 ml / l of water gave the best response to the number of filled pods (16.50), number of grains (48.63 grains), and grain weight (18.30 g).